'Doing what's best at the time' : first-time mothers learning to breastfeed away from home : a grounded theory study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Nursing at Massey University - Kennedy, Angela E (Massey University, 2000)
In order to explore what was happening for nine first-time mothers, as they breastfed away from home, the study was carried out when the mothers were still breastfeeding at between six and twelve weeks following the birth of their infants. Grounded theory methodology underpinned the way in which the data were collected, analysed and presented. Semi-structured interviews were used to provide the participants with an opportunity to talk about the reality, for them, of breastfeeding away from their own home environment. Emerging from the data was a picture of mothers learning to breastfeed, acknowledging that they needed to feel confident with their breastfeeding. As a result they remained in the privacy of their home in the early days and weeks after birth, limiting their social interaction while they gained confidence with breastfeeding. When the mothers felt more confident they moved out of the home into many different social situations, while integrating breastfeeding into their daily lives. The mothers gained a sense of achievement by learning to meet challenges of social interaction, giving them increased confidence as new mothers and encouragement to continue breastfeeding. If the mothers did not feel confident or comfortable breastfeeding in certain social situations, they planned to avoid them by working around breastfeeding at home. When situations arose away from home in which they did not feel comfortable breastfeeding, they chose to postpone breastfeeding or to withdraw to privacy to enable breastfeeding to continue. The mothers read each situation as it unfolded and chose actions which were indicative of protecting themselves and others from discomfort or embarrassment.
Keywords: Breastfeeding; New Zealand